Dietary n-3 polyunsaturated fatty acids improve endothelial markers in metabolic syndrome: A systematic review - Bertorello, Natalia Belén (2022)
Metabolic syndrome (MS) is a global health problem. Dietary factors, especially fatty acids, may affect MS pathology. However, the associations between omega-3 polyunsaturated fatty acids (n-3 PUFAs) and MS risk demonstrate inconsistent results. To clarify the relationship between dietary n-3 PUFA and endothelial function on MS, we carried out a systematic review. An electronic literature search based on controlled clinical trials (CCTs) between 2004 and 2020 was conducted. A total of 28 articles were included in the systematic review. Studies were analyzed according intervention type: dietary interventions (12 CCTs), dietary supplementation interventions (9 CCTs) and mixed interventions (7 CCTs). Studies with dietary interventions characterized by n-3 PUFAs increased by food source, such as Mediterranean and Nordic-style diets, reported significant reduction in systolic and diastolic blood pressure, and also in inflammatory endothelial biomarkers. The same effect was also observed in mixed interventions and in CCTs with n-3 PUFAs supple-mentation. Dietary interventions with n-3 PUFAs contributes to improved endothelial and cardiovascular health in SM and associated risk factors.